FVC, FEV1 and FEV1/FVC%, In Postmenopausal Women and Their Relationship with Serum Progesterone and Estrogen Level - Polly, Zinat Ara; Begum, Shelina; Ferdousi, Sultana; Begum, Noorzahan; Ali, Taskina; Begum, Afroza (Journal of Bangladesh Society of Physiologist, 2009)
Background: Exacerbation of asthma associated with worsening of lung function has been reported in women after menopause. The relationship between lung function and female sex hormones has been documented in postmenopausal women. Objective: To observe FVC, FEV1, FEV1/FVC%, serum estrogen and progesterone levels in apparently healthy postmenopausal women to find out their interrelationships. Methods: This cross sectional study was carried out in the Department of Physiology, from 1st January 17to 31st December 2007 in BSMMU, Dhaka. 30 postmenopausal women aged 45 to 60 years and 30 premenopausal women aged 20 to 30 years during different phases of menstrual cycle were studied. FVC, FEV1 and FEV1/FVC%, were measured by RMS computer based Spirometer. Estrogen and progesterone levels were estimated by Micro particle Enzyme Immunoassay (MEIA) method. Data were analyzed by Pearson's correlation coefficient test, one way ANOVA and unpaired‘t' test. Results: The mean percentage of predicted values of FVC and FEV1 were significantly (p<.001) lower in postmenopausal women compared to those of follicular and luteal phases of premenopausal women. Mean serum estrogen and progesterone levels were significantly lower in postmenopausal women compared to any phases of menstrual cycle of premenopausal women. In postmenopausal women, FVC, FEV1 showed positive correlation with progesterone but negative with estrogen level.FEV1/ FVC% Showed negative correlation with both serum estrogen and progesterone level. All these correlations were statistically non significant. In premenopausal women FEV1 and FEV1/FVC% showed positive correlation and FVC showed negative correlation with serum estrogen level in follicular phase and FVC, FEV1 showed positive and FEV1/FVC% showed negative correlation with serum estrogen level in luteal phase. Again FVC, FEV1 and FEV1/FVC% showed positive correlation with serum progesterone level in follicular and luteal phases of menustrual cycle. Conclusion: The out come of this study shows FVC, FEV1 may be reduced in postmenopausal women which in turn may be associated with low progesterone and estrogen levels. Key words: Menopause, Lung function, Estrogen, Progesterone. DOI: 10.3329/jbsp.v4i1.4063 J Bangladesh Soc Physiol. 2009 June; 4(1): 7-13